2018
DOI: 10.1002/acn3.638
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain serum levels correlate with 10‐year MRI outcomes in multiple sclerosis

Abstract: ObjectiveTo assess the value of annual serum neurofilament light (NfL) measures in predicting 10‐year clinical and MRI outcomes in multiple sclerosis (MS).MethodsWe identified patients in our center's Comprehensive Longitudinal Investigations in MS at Brigham and Women's Hospital (CLIMB) study enrolled within 5 years of disease onset, and with annual blood samples up to 10 years (n = 122). Serum NfL was measured using a single molecule array (SIMOA) assay. An automated pipeline quantified brain T2 hyperintense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
142
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(153 citation statements)
references
References 39 publications
6
142
4
1
Order By: Relevance
“…Our findings of higher baseline sNfL levels, higher concurrent inflammatory activity, and future WBV atrophy are in line with several previous reports . Associations between baseline sNfL levels, T 2 ‐LV, and Gd–enhancing lesions have been demonstrated as early as at the first demyelinating event, and are able to significantly predict conversion to clinically definite MS .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of higher baseline sNfL levels, higher concurrent inflammatory activity, and future WBV atrophy are in line with several previous reports . Associations between baseline sNfL levels, T 2 ‐LV, and Gd–enhancing lesions have been demonstrated as early as at the first demyelinating event, and are able to significantly predict conversion to clinically definite MS .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, studies report up to 17.8% and 4.9% increase in sNfL levels for every Gd–enhancing lesion and new/enlarging T 2 lesion, respectively . In a 10‐year follow‐up study, sNfL levels measured at the 5‐year time point were associated with greater WBV loss till year 10 . Correspondingly, a 5‐year longitudinal study showed similar sNfL effect size and associations with greater WBV atrophy measured both at 2 and 5‐year follow‐up .…”
Section: Discussionmentioning
confidence: 74%
“…High NfL levels in blood were also associated with higher risk of future relapses and EDSS worsening . Blood NfL levels predicted disability worsening after up to 8 years and lesion load and atrophy after 10 years in patients with MS . Notably, NfL predicted future brain and spinal cord atrophy .…”
Section: Discussionmentioning
confidence: 91%
“…However, a number of studies have shown that blood NfL levels are significantly higher in patients with MS and were reduced after treatment with fingolimod, natalizumab, and rituximab in CSF but also in several observational studies in the blood . NfL levels at baseline correlate with clinical (such as a recent relapse and an EDSS score) as well as MRI‐related measures (such as T2 lesion volume and number of gadolinium‐enhancing lesions and brain volume loss) . High NfL levels in blood were also associated with higher risk of future relapses and EDSS worsening .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore interesting that even early measures of blood NF-L in newly diagnosed MS patients can predict brain atrophy [22] and lesion load on MRI [23], probably reflecting high disease activity since this can be modified by initiation of effective treatment [108]. However, NF-L levels have shown poor correlation to disability scores such as the Extended Disability Status Scale (EDSS) [22][23][24]93,109,110]. This is most likely due to the emphasis on gait performance in the EDSS that may overestimate the influence of spinal cord lesions over cerebral lesions, which can be extensive even at low EDSS scores.…”
Section: Multiple Sclerosismentioning
confidence: 99%